Penyelesaian Konflik Keluarga Melalui Mediasi di Indonesia dan Malaysia: Kajian Sosiologi Hukum Islam - Ismayawati , Any; Aristoni; Chaedar, Syed Mohammad (Jurnal Hukum Islam, 2024)
Integration of mediation or sulh into the judicial system is still believed by the Indonesian and Malaysian people as the right instrument in resolving family conflicts because it offers a humanistic and constructive approach that can solve problems without problems. However, in practice, it is faced with several problems that cause mediation or sulh to be ineffective. This study explores the dynamics of the application of mediation or sulh in resolving family conflicts in Indonesia and Malaysia, which is analyzed using the Islamic legal sociology approach as the basis for the study. The research method uses a sociology of law with a qualitative approach. Data sources were obtained through interviews and literature studies. The results show, the dominant factors influencing the ineffectiveness of the application of mediation or sulh in resolving family conflicts in both countries include: some mediators or sulh employees still have weaknesses in interpersonal skills, limited certified mediators, and the lack of good faith of the parties attending the mediation or sulh process. The sociology of Islamic law views that this reality reflects the weakness of legal structure and culture in complying with mediation regulations and practicing Islamic law. Concrete steps in addressing the root of the problem are needed by improving the quality and quantity of mediators or sulh employees, as well as providing legal education to the community. This study contributes to improving the quality of mediation in the Court as well as to the formation of regulations on mediation.